2008
DOI: 10.1590/s0085-56262008000400022
|View full text |Cite
|
Sign up to set email alerts
|

Necrológio: José Henrique Guimarães (08.10.1937 - 14.10.2008)

Abstract: Em 1966 foi contemplado com uma bolsa de estudo da "John Simon Guggenheim Memorial Foundation", para fazer uma especialização em Entomologia na Smithsonian Institution, sob orientação do Dr. Curtis Sabrosky. Ali passou o ano de 1967, principalmente elaborando o catálogo dos Tachinidae neotropicais, publicado em 1971 (a família contava, então, com 2864 espécies e 944 gêneros), com 333 páginas. Anos antes (1967) havia já publicado os catálogos neotropicais de Gasterophilidae, Oestridae e Cuterebridae. Estendeu s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…These species were a direct result of the revision of Trichodura: T. amazonensis Guimarães, 1972, T. friburguensis Guimarães, 1972, T. longicauda Guimarães, 1972, T. sabroskyi Guimarães, 1972and T. townsendi Guimarães, 1972 Later, Guimarães moved to the Department of Parasitology of the University of São Paulo (São Paulo). At this institution, he developed studies in the areas of urban entomology and veterinary entomology, retiring in 1993 to later return to MZUSP, where he continued his research, curation and supervision activities (Lamas et al, 2008). Guimarães' legacy will remain intact, as the tribes and genera reviewed by him are the tachinids most prone for studies on evolution and the most indicated to further develop their potential as biological control, as they are readily recognized and all of their names and identities are clear and resolved.…”
Section: Latin American Dipterists Enter the Scene: Brèthes Blanchard...mentioning
confidence: 99%
“…These species were a direct result of the revision of Trichodura: T. amazonensis Guimarães, 1972, T. friburguensis Guimarães, 1972, T. longicauda Guimarães, 1972, T. sabroskyi Guimarães, 1972and T. townsendi Guimarães, 1972 Later, Guimarães moved to the Department of Parasitology of the University of São Paulo (São Paulo). At this institution, he developed studies in the areas of urban entomology and veterinary entomology, retiring in 1993 to later return to MZUSP, where he continued his research, curation and supervision activities (Lamas et al, 2008). Guimarães' legacy will remain intact, as the tribes and genera reviewed by him are the tachinids most prone for studies on evolution and the most indicated to further develop their potential as biological control, as they are readily recognized and all of their names and identities are clear and resolved.…”
Section: Latin American Dipterists Enter the Scene: Brèthes Blanchard...mentioning
confidence: 99%
“…The Brazilian José Henrique Guimarães (1937Guimarães ( -2008 was educated at agricultural schools in Rio de Janeiro before beginning the study of Tachinidae as an intern at the Laboratório de Zoologia Médica e Parasitologia da Escola Nacional de Veterinária and the Instituto Oswaldo Cruz, in Rio (Lamas et al 2009). A series of five revisionary papers on Archytas resulted from these studies (Guimarães 1960(Guimarães , 1961a(Guimarães , b, 1963a in addition to several papers on other tachinine tachinids.…”
Section: A Historical Perspective On the Tachinidae Of Chilementioning
confidence: 99%
“…With that completed he returned to Brazil in 1970 to resume his former position and to begin study of the Mesembrinellidae for a Ph.D. degree, completed in 1973. Guimarães remained at the Museu de Zoologia until 1985 and then moved on to other positions before retiring in 1993 (Lamas et al 2009). His sole-authored papers on Tachinidae ended in 1983 but he assisted with other tachinid papers up to 2002.…”
Section: A Historical Perspective On the Tachinidae Of Chilementioning
confidence: 99%
“…Nelson Papavero says that when Carrera retires, he leaves the collection with around twenty-five thousand specimens. His position is then occupied, in January 1963, by José Henrique Guimarães (1937Guimarães ( -2008, a world-renowned researcher in the study of the Diptera of the Tachinidae family (Lamas et al, 2008).…”
Section: Professional and Academic Developmentmentioning
confidence: 99%